ICT critical infrastructures and society 10th IFIP TC 9 International Conference on Human Choice and Computers, HCC10 2012, Amsterdam, The Netherlands, September 27-28, 2012. Proceedings - Hercheui, Magda David (IFIP Advances in Information and Communication Technology, 2012)
This book constitutes the refereed proceedings of the 10th IFIP TC 9 International Conference on Human Choice and Computers, HCC10 2012, held in Amsterdam, The Netherlands, in September 2012. The 37 revised full papers presented were carefully reviewed and selected for inclusion in the volume. The papers are organized in topical sections on national and international policies, sustainable and responsible innovation, ICT for peace and war, and citizens' involvement, citizens' rights and ICT.